Physiological demands of elite team handball with special reference to playing position - Povoas, S. C. A.; Ascensão, A. A. M. R.; Magalhaes, J.; Seabra, A. F.; Krustrup, P.; Soares, J. M. C.; Rebelo, A. N. C. (The Journal of Strength and Conditioning Research, 2014)
This study aimed to analyze the physiological demands of match play for different playing positions in elite male team handball. Time motion (N = 30) and heart rate (HR; N = 70) data were recorded throughout 10 official matches. The mean distance covered by backcourt players (4.96 ± 0.64 km) was greater (p kleiner/gleich 0.02) than for wings and pivots (4.23 ± 0.52 and 3.91 ± 0.51 km, respectively). Backcourt players spent less time standing still and walking (~76%) than wings and pivots (?80%) (p kleiner/gleich 0.03), and wings spent more time sprinting than the other playing positions. Backcourt players (122.9 ± 17.0) and pivots (126.8 ± 33.0) performed more high-demanding actions per game than wings (54.6 ± 15.6) (p = 0.01). The time spent by pivots in high-intensity activities decreased from the first to the second half (4.1 ± 2.4 to 2.7 ± 0.9%; p kleiner/gleich 0.01), while backcourt players showed a decrease in high-demanding playing actions (p kleiner/gleich 0.05). Backcourt players and pivots had higher mean (84 ± 9 and 83 ± 9% vs. 79 ± 10%; p kleiner/gleich 0.03) and peak effective HR, and percentage of total time at intensities >80% maximal HR (HRmax) than wings. The fraction of total time spent at intensities >80% HRmax decreased for all outfield playing positions in the second half (from 39-76 to 30-46%). Competitive team handball involves position-specific differences in the physiological demands. Furthermore, exercise intensity decreases from the first to the second half for all outfield playing positions suggesting that these players experience neuromuscular fatigue. Training of elite handball players should comprise high-intensity position-specific exercises aiming at improving the ability to maintain a high exercise intensity throughout the game.